PC.01 Outcomes following the diagnosis of Hypoplastic Left Heart Syndrome; changes over a 15 year period. (9th June 2014) - Peake, L; Draper, E; Field, D
Abstract : Background: Anecdotally, outcomes in patients with hypoplastic left heart syndrome (HLHS) are poor but improving. Most outcome data has come from specialist centres, excluding patients who die before transfer. Long term outcomes are generally not reported. Methods: We studied cases of HLHS born from a geographical population (Leicestershire) over a 15 year period (01/01/1998–31/12/2012), using information from a congenital anomaly register (EMSYCAR) and a register of surgical patients from the East Midlands Congenital Heart Centre. Data were collected on: diagnosis, pregnancy and birth outcomes, indicators of perinatal morbidity, surgical outcomes and long term morbidity (medication, continuing symptoms, neurodevelopmental impairment). Results: 55 cases where identified, 33 resulting in a live birth (1.94 per 10, 000 live births, 95% CI: 1.32–2.67). 79% of cases were detected antenatally. Max and mean follow up was 13.5 and 6.25 years respectively. Patients born alive between 1998 and 2002 and who later died had a median survival of 2 days (IQR: 1–3). Median survival was improved to 26 days in patients born between 2008 and 2012 (IQR: 10.5–58.5). 10-day survival was significantly improved between the two groups; 6 month, 1 year and 3 year survival was improved, but not significantly. No deaths were found in patients who survived beyond 4 months. Conclusions: Advances in medical and surgical treatment of HLHS has significantly improved short term life expectancy. Longer term survival shows a trend toward improvement, but this change was not significant over the past 15 years.